O fenômeno e a estrutura da mente consciente: as relações de integração entre consciência, cérebro, corpo e meio ambiente - Rodrigues, Edmar Gomes (2014)
Through this dissertation, our proposal is to maintain that consciousness, one of the most remarkable aspects of human life, emerges from the integrated activity between brain, body and its environment, without consciousness be confused with the totality of our neurophysiological activity. We also propose to argue that consciousness is the most sophisticated expression of our mental life, which is why the concepts of consciousness and mind are neither separable nor confused. To this end, we propose to show that mental activity is not necessarily conscious, and either depends on a highly evolved brain, since its function, as demonstrated by Damasio, is to maintain homeostasis and manage organic life in its fullness. In association with this task, we aim to support the ideia that consciousness is an emergent activity of the combination of specialized neural programs , and the thesis that consciousness goes back to our innate abilities to solve immediate problems. From there, we intend to maintain that consciousness develops from sophisticated cognitive processes, and of the tireless interactions of the brain with amendments that are either internal or external in relation to the organism. We also propose to demonstrate, through our discussions, that the information into consciousness acquire emotional valence by combining of a set of feelings of emotion whose function is to interpret, refresh and strengthen the constant organism s changes. We want to show that it is solely through strengthening and particularization of information intensified by feelings that the organism recognizes itself as subject and author of its own experiences. Thus, what one is the self and what one thinks the consciousness states depend on development and healthy and comprehensive interaction of the organism (brain and body itself) with environment, internal and external. This interaction is naturally featured by the brain, and this fact does not justify, as is well shown by Damasio, a cerebralist perspective of mind.